Natural Regeneration After Volcanic Eruptions: Resilience of the Non-legume Nitrogen-Fixing Tree Parasponia rigida - Ishaq, Rizki M.; Hairiah, Kurniatun; Alfian, Ibnu; van Noordwijk, Meine (Frontiers in Forests and Global Change, 2020)
Volcanic eruptions disturb vegetation at a time it is needed for preventing mudflows. A resilient indigenous non-legume nitrogen-fixing tree that is adapted to the ash and spreads rapidly protects areas downstream in a volcanic landscape in Indonesia. Mount Kelud in East Java has erupted on a 15-37-year cycle for the past centuries, most recently in 2014, causing damage to settlements, agricultural land, agroforestry, and watershed protection forests, as the ash deposits caused tree mortality, restricted infiltration, and led to ash flows. Rapid ‘restoration’ or recovery of tree-based vegetation with planted Legume trees (such as Calliandra spp) has been attempted but is not very effective. However, the non-legume nitrogen-fixing Parasponia rigida, symbiotic with rhizobium bacteria, contrasted to its non-symbiotic sibling (Trema orientalis) has been studied in laboratory conditions, but not in its native environment. We mapped and sampled P. rigida in various locations (upper, middle, and lower elevation positions in ridge-slope-valley toposequences) on the Kelud complex starting one year after the latest eruption, estimated biomass development, and quantified P. rigida root nodules in relation to N availability in the ash/soil mixtures in these locations. P. rigida was found as a pioneer tree at elevations between 600 and 1700 m a.s.l. (above sea level) along ridges, in slope, and valley positions. At lower elevations T. orientalis dominated. Within three years of the eruption, stem diameters were 3 - 10 cm. Up to 93% of P. rigida root nodules were found to be effective, based on the hemoglobin colour on cross-sections. Rhizobium bacteria were found in root nodule tissue at densities of two to a hundred times higher than in rhizosphere soil. Between a total soil N content from 0.01 to 0.04% the density of effective nodules decreased from 1200 to 200 m-2. P. rigida stands in the area, especially at ridges close to the crater deserve to be managed proactively as future seed sources, given the high frequency of eruption episodes, while recovery after eruptions on similar volcanoes can likely be facilitated by tactical assisted seed dispersal if effective seed collection and storage methods can be established.